Relationship between traumatic dental injuries and attention-deficit/hyperactivity disorder in children and adolescents: proposal of an explanatory model - SABUNCUOĞLU, OSMAN TALAT (BLACKWELL PUBLISHING, 2005)
The objective of the present study was to determine the association between attention-deficit/hyperactivity disorder (ADHD) and traumatic dental injuries in a child psychiatric clinical population in Istanbul. A total of 475 consecutive children aged 8-17 years were enrolled in the study. Children and their parents were interviewed about the presence of traumatic dental injury and if a positive response was obtained further questions were inquired regarding the time and cause of the injury, and whether treatment had been sought. Child psychiatric diagnosis was based on Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) criteria. Of the 475 children, 32 reported a traumatic dental injury (6.7%) with statistically significant association with ADHD (chi(2) = 26.90, d.f. = 1, P = 0.0001; odds ratio = 17.41, 95% CI: 4.11-73.55). On the Conners Teacher Report Questionnaire, children with dental trauma group differed significantly from the non-ADHD group but not from the ADHD group (F = 17.02, d.f. = 2, P = 0.0001). Among children with ADHD and dental fracture, the most common subtype was combined ADHD (90%). This is the first study describing a significant association between dental fractures and ADHD which contributes to an explanatory model on dental traumas among children. According to us, awareness of this association is essential at child psychiatry and pediatric dentistry settings and we recommend preventive efforts to be directed at the treatment of ADHD.
Keywords: dental trauma; tooth injuries; attention deficit; hyperactivity disorder (ADHD); RISK-FACTORS; TEETH; PREVALENCE